2021
DOI: 10.3906/sag-2106-190
|View full text |Cite
|
Sign up to set email alerts
|

How efficient are facial masks against COVID-19? Evaluating the mask use of various communities one year into the pandemic

Abstract: Face masks are devices worn over the mouth and nose to protect against splashes, infectious respiratory droplets or aerosols generated during breathing or coughing according to their filtering capacity. Medical masks, respirators or cloth masks have been used for source control and for the protection of the exposed. After the first case on March 11, 2020, in Turkey, National COVID-19 Scientific Advisory Board published various contents for the correct use of masks. Medical face masks have been used in healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…20 Researchers recommend a regular change of facemasks for improved effectiveness. 21 A study found that wearing a surgical mask can decrease the probability of Covid-19 disease by 56%. 22 A meta-analysis reported that N95 or similar masks have an effectiveness of up to 70.0% because of the risk of SARS-CoV-2 disease in comparison to approximately 30.0% for surgical or medical masks.…”
Section: Performance Of Personal Protective Measures Against Coronavi...mentioning
confidence: 99%
“…20 Researchers recommend a regular change of facemasks for improved effectiveness. 21 A study found that wearing a surgical mask can decrease the probability of Covid-19 disease by 56%. 22 A meta-analysis reported that N95 or similar masks have an effectiveness of up to 70.0% because of the risk of SARS-CoV-2 disease in comparison to approximately 30.0% for surgical or medical masks.…”
Section: Performance Of Personal Protective Measures Against Coronavi...mentioning
confidence: 99%
“…Los EPI y la percepción adecuada de las personas frente al uso de estos han demostrado que disminuyen la transmisión de la infección por SARS-CoV-2 (19)(20)(21) . Sin embargo, la efectividad se ve reducida cuando la utilización no es la correcta o existe poca adherencia a estos (22) . Por otro lado, existe escasa evidencia del nivel de conocimiento de la COVID-19, las medidas de bioseguridad y el uso correcto de los EPI en países de baja o media renta.…”
Section: Introductionunclassified
“…Social distancing encompasses 3 of the CDC recommended behaviors: maintaining 6 feet distance when around other people, avoiding close contact with those outside of one’s household, and avoiding contact with individuals who are sick. The majority of efficacy studies have focused on the effectiveness of social distancing and mask-wearing [ 20 , 21 , 57 ]. More recent studies have reconfirmed the efficacy of mask-wearing in reducing the risk of COVID-19 infection [ 57 ].…”
Section: Introductionmentioning
confidence: 99%